Meningkatkan Keterampilan Menulis Deskripsi dengan Model Picture and Picture di SDN 3 Bangkleyan Kabupaten Blora - Ahmad Sholeh; Veryliana Veryliana; Darsimah Darsimah (Universitas Pendidikan Mandalika, 2021)
The purpose of this study was to improve teacher skills, increase student activity, and improve student learning outcomes in writing descriptions through the application of the Picture and Picture model. This classroom action research was carried out in 3 cycles, each cycle consisting of 2 meetings. The subjects of this study were the teacher and 18 second grade students of SDN 3 Bangkleyan. The research data in the form of quantitative data and qualitative data were analyzed using descriptive analysis techniques. From the results of the study it can be concluded that: (1) the skills of teachers in the first cycle got an average score of 29 with good criteria and in the second cycle got an average score of 31 with good criteria, the third cycle got an average score of 35 with very good criteria. (2) student activities in cycle I obtained an average score of 24 with sufficient criteria, in cycle II obtained an average score of 27 with good criteria, and in cycle III obtained an average score of 30 with good criteria. (3) student learning outcomes in the form of descriptive writing skills at the end of the first cycle obtained an average value of 65.5 and classical learning completeness 50%, in the second cycle an average value of 69 and classical learning completeness of 69.4% cycle III got an average score of 79 and classical learning completeness of 83.3%.